Pengaruh Penggunaan Media Audio Visual TerhadapPenguasaan Kosa Kata Bahasa Inggris Padakelompok B Tk Aisiyahbustanul Atfal Ngasem ColomaduKaranganyartahun Ajaran 2015/2016 - Arguningrum, Fantra Anggun (2016)
In the current era of globalization, English language skills play an important role that should be introduced to children. It supported the policy by Curriculum StructureandCompetence StandardClass in Englishrefers toLawNo.20 of 2003 onNational Education System. WhereClass in EnglishasLocal Content. Competency standardssubjects in Englishis aprogramto develop the knowledge, language skills, anda positive attitudetowardsEnglish. Media early childhood learning one of them with audio-visual media are many aspects that can be developed in children namely cognitive, motor, social, emotional, language, religious moral values and so on. From one in that aspect, in the aspect of language can be seen through the mastery of vocabulary. The purpose of this study to determine the effect of the use of audio-visual media to the mastery of the English vocabulary.This research method using the experimental method. The study can be seen through the increase in the percentage of the initial observation score 25.84%, 47.36% giving treatment and final observations 51.26%. In this research has proved that the use of audio-visual media affect mastery of English vocabulary in children. Keywords: audio visual, vocabulary, the child's developmen